Melanosis of the vagina and human papillomavirus infection, an uncommon pathology: Case Report - Núñez Troconis, José; Delgado, Mariela; González, Gerardo; Rivas, Airiaudis; Molero, Katherine (Investigación Clínica, 2012)
Benign melanotic lesions of the vagina are uncommon and only a few cases have been reported in the literature. A 34-year-old woman was referred because of a Vaginal Intraepithelial Neoplasia 1 biopsy result. On the gynecological examination, two different hyperpigmented areas were noted in the vagina. The colposcopic visualization of the cervix and vagina found an aceto-white lesion at the right lateral wall of the upper third of the vagina. Biopsies from three areas were taken. Histological study reported a melanosis of the vagina and HPV infection. An immunohistochemical panel of epithelial markers was performed in vaginal samples, such as Cytokeratin AE1/AE3 and epithelial membrane antigen, mesenchymal marker: vimentin; melanocytic makers: protein S-100 and HMB45 (Human Melanoma Black); proliferating cell marker: proliferating cell nuclear antigen (PCNA), and P-53 oncoprotein. High Risk (16, 18, 31, 45) and Low Risk (6, 11) HPV types were studied by In Situ Hybridization using the same vaginal samples. CK, EMA and Vimentin were 2+. Melanocytic markers, HMB45 and S100, and PCNA were 1+ in basal cell layer. P-53 was negative. The melanotic tissue and acetowhite lesion were positives to HPV Types 6,11. In conclusion, melanosis of the vagina is a uncommon benign pathology. Usually, melanosis is present in women over 40 years old. We present a case of melanosis of the vagina in a young woman infected with low-risk HPV types and review the literature.